Perception of parents on the implementation of compulsory of schooling; a case study in Kuching, Sarawak / Arthur Sigoh... et.al - Sigoh, Arthur; Stanley, Benny; Belawing, Cliff; Usit, Henry; Janting, Nigel (Universiti Teknologi Mara Cawangan Sarawak, 2002)
This research shows the result of our research toward the Perception Of Parents On The Implementation Of Compulsory Schooling. The hypothesis that we used to test the research of the parents view pre-education as important for their child. Parents viewed at with the implementation of compulsory education; the rate of illiteracy can be minimized and drop out rates of students in rural areas are more than students in the urban area. There are 200 respondents take parts in our research especially in the Kuching Division. The questionnaires that we have distributed are used to collect information for purpose of data analysis and research. The questionnaires are divided into sections in which all the questions are related and easy to us to interpret the data. The analysis and the hypothesis in the research are through statistic method such as the percentage and the table that used to give us the view of the research. The result of the findings show that the parents give fully support toward the compulsory education, the factors and the recommendations of illiteracy rates can be minimized through this compulsory education and the drop-out rates in the rural area are more than in the urban area.